Editorial statement for mathematical finance - Wing Keung Wong (Journal of Risk and Financial Management, 2020)
Mathematics plays a vital role in many areas of finance and provides the theories and tools that have been widely used in all areas of finance. In this editorial, we tell authors the ideas on what types of papers we will accept for publication in the area of mathematical finance. We will discuss some well-cited papers of mathematical finance.
Keywords: 330; applications; finance; mathematics; probability; statistics